Nanodiamond‐Mediated Intercellular Transport of Proteins through Membrane Tunneling Nanotubes. Issue 45 (19th October 2015) - Epperla, Chandra Prakash; Mohan, Nitin; Chang, Che‐Wei; Chen, Chia‐Chun; Chang, Huan‐Cheng
Abstract : Recently discovered tunneling nanotubes (TNTs) are capable of creating intercellular communication pathways through which transport of proteins and other cytoplasmic components occurs. Intercellular transport is related to many diseases and nanotubes are potentially useful as drug‐delivery channels for cancer therapy. Here, we apply fluorescent nanodiamond (FND) as a photostable tracker, as well as a protein carrier, to illustrate the transport events in TNTs of human cells. Proteins, including bovine serum albumin and green fluorescent protein, are first coated on 100‐nm FNDs by physical adsorption and then single‐particle tracking of the bioconjugates in the transient membrane connections is carried out by fluorescence microscopy. Stop‐and‐go and to‐and‐fro motions mediated by molecular motors are found for the active transport of protein‐loaded FNDs trapped in the endosomal vehicles of human embryonic kidney cells (HEK293T). Quantitative analysis of the heterotypical transport between HEK293T and SH‐SY5Y neuroblastoma cells by flow cytometry confirm the formation of open‐ended nanotubes between them, despite that their TNTs differ in structural components. Our results demonstrate the promising applications of this novel carbon‐based nanomaterial for intercellular delivery of biomolecular cargo down to the single‐particle level. Abstract : Tunneling nanotubes (TNTs) provide a unique intercellular communication pathway through which transport of proteins, vesicles, and organelles occurs. Using fluorescent nanodiamond (FND) as a photostable and biocompatible marker, this work successfully tracks protein‐loaded FNDs along the TNTs of human cells and demonstrates its potential use for the intercellular delivery of biomolecular cargo at the single‐particle level.